2014
DOI: 10.1089/omi.2013.0133
|View full text |Cite
|
Sign up to set email alerts
|

TCTEX1D4 Interactome in Human Testis: Unraveling the Function of Dynein Light Chain in Spermatozoa

Abstract: Studies were designed to identify the TCTEX1D4 interactome in human testis, with the purpose of unraveling putative protein complexes essential to male reproduction and thus novel TCTEX1D4 functions. TCTEX1D4 is a dynein light chain that belongs to the DYNT1/TCTEX1 family. In spermatozoa, it appears to be important to sperm motility, intraflagellar transport, and acrosome reaction. To contribute to the knowledge on TCTEX1D4 function in testis and spermatozoa, a yeast two-hybrid assay was performed in testis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Other dynein light chains have been described in spermatogenesis. For the dynein light chain tctex-type 4 (DNLT4), 40 different interactors have been identified in human testis, showing the functional variety of dynein light chain interacting proteins (Freitas et al, 2014). In human, absence or lower levels of dynein light chain tctex-type 1 (DNLT1), have been associated with male infertility (Indu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other dynein light chains have been described in spermatogenesis. For the dynein light chain tctex-type 4 (DNLT4), 40 different interactors have been identified in human testis, showing the functional variety of dynein light chain interacting proteins (Freitas et al, 2014). In human, absence or lower levels of dynein light chain tctex-type 1 (DNLT1), have been associated with male infertility (Indu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…IFT88 interactome was retrieve from several databases and TCTEX1D4 was added to the interactome since IFT88 was identified as a TCTEX1D4 interactor [14]. Most interactors were identified by indirect methods; therefore these interactions must be confirmed by direct methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IFT88 has also been linked to migration and invasion of hepatoma cells [11], to olfactory function [12], spindle formation [8], and to mitosis (a non-cilium function) [13]. Recently a yeast two hybrid screen performed in our laboratory revealed that, in testis, IFT88 interacts with TCTEX1D4 (t-complex testis expressed 1 domain containing 4), a dynein light chain from the DYNT1/TCTEX1 family [14]. TCTEX1D4 was first described as an interactor of several components of the TGFbeta pathway [15].…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes a dynein light chain protein that belongs to the TCTEX1 family. Freitas et al (2014) discussed its role in sperm motility and IFT.…”
Section: Gene Groupsmentioning
confidence: 99%